PENGENALAN INTERNET SEHAT PADA SMAN I TIGAPANAH, KABUPATEN KARO, SUMATERA UTARA - Fati Gratianus Nafiri Larosa; Humuntal Rumapea; Indra M. Sarkis S.; Yolanda Yulianti Pratiwi Rumapea; Edward Rajagukguk; Darwis Robinson Manalu; Doli Hasibuan; Jhoni Maslan; Surianto Sitepu; Arina Prima Silalahi; Posma Lumbanraja; Nettina Samosir; Gresa Simarmata; Putra Palipi (Universitas Methodist Indonesia, 2021)
A healthy Internet is one of the basic needs of the use of digital technology in various fields, especially in the world of education. Since SMAN I is one of the service partners and is also very close to the center of agriculture and tourism, Community is carried out by the Information System Study Program, Universitas Methodist Indonesia as a form of implementing the Tri Dharma of Higher Education. Its purpose and benefits are to share and contribute ideas and transfer knowledge and technology. This service activity was carried out for a day, with the material including explanations about Internet Sehat (Healthy Internet) and Internet Cakap. This topic is very much needed in the education community to be able to use the internet intelligently, creatively, and productively.